2022
DOI: 10.1097/olq.0000000000001638
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Chlamydia and Gonorrhea Tests Performed by a Large National Laboratory—United States, 2019 to 2020

Abstract: Comparing April 2019 and April 2020, the number of chlamydia tests declined by 53.0% overall (54.1% in stay-at-home states vs. 45.5% others, P < 0.05). Percent positive increased by 23.5% for chlamydia and 79.1% for gonorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
3
14
1
Order By: Relevance
“…However, in contrast to our hypothesis that screening would have made up a smaller proportion of STI testing due to the pandemic restrictions, screening tests actually made up a larger proportion of the testing done during the early pandemic compared to earlier time periods. Hence, while other data suggested that screening decreased more than symptomatic testing during the early COVID-19 pandemic due to increased positive test rates, our data do not support this [4][5][6].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, in contrast to our hypothesis that screening would have made up a smaller proportion of STI testing due to the pandemic restrictions, screening tests actually made up a larger proportion of the testing done during the early pandemic compared to earlier time periods. Hence, while other data suggested that screening decreased more than symptomatic testing during the early COVID-19 pandemic due to increased positive test rates, our data do not support this [4][5][6].…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to prior studies, we found that overall STI testing decreased for adolescent females during the early phase of the COVID-19 pandemic compared to pre-pandemic levels [3][4][5][6]. However, in contrast to our hypothesis that screening would have made up a smaller proportion of STI testing due to the pandemic restrictions, screening tests actually made up a larger proportion of the testing done during the early pandemic compared to earlier time periods.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These findings are in line with other qualitative findings from SSPs in the United States [ 14 , 15 , 20 ]. Additionally, during the COVID-19 pandemic there was a national decrease in STI screening [ 21 23 ] and an increase in incidence of STIs [ 22 , 24 ]. The use of at-home HIV tests by a program in this study provides one pathway for encouraging HIV testing among PWID during times of prolonged service disruption at SSPs.…”
Section: Discussionmentioning
confidence: 99%